Visualization of the Anticaging Effect of Ronozyme WX Xylanase on Wheat Substrates. Issue 5 (2nd October 2013) - Le, Duy Michael; Fojan, Peter; Azem, Elisabeth; Pettersson, Dan; Pedersen, Ninfa Rangel
ABSTRACT: A fluorescence microscope was used for visualization of the anticaging effect of a commercial xylanase on milled wheat, microtome cuts of wheat grains, and digesta samples obtained from piglets 1 or 4 h after feeding a wheat‐based diet (wheat 490 g/kg of diet, barley 100 g/kg of diet, and oats 100 g/kg of diet). Both starchy endosperm and aleurone cell walls were shown to be broken down by Ronozyme WX commercial xylanase. Data obtained by fluorescence microscopy was supplemented with measurements of starch and xylose released as a result of degradation of nonstarch polysaccharides by the xylanase. The results visualize and provide evidence that Ronozyme WX commercial xylanase can overcome the so‐called cage effect. This release of nutrients from their encapsulation in cereal cell wall structures has positive impact on nutrient digestibility and partially explains the positive effect of xylanase supplementation on livestock performance.